APRESENTAÇÃO - Camargo Vianna, Cintia; Canavarro Benite, Anna Mª; Otaviana Barbosa de Sá Figueiredo, Mércia; Novaes da Silva, Antonio (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Prezadas/os Leitoras/es,